Pengembangan Pembelajaran Daring Melalui Media Interaktif Simulasi Elektronik (MISE) pada Mata Kuliah Ekonomi Makro - Mayasari Mayasari (Universitas Batanghari Jambi, 2021)
There are two objectives achieved in this research, including: 1) developing tools for developing online learning through electronic simulation interactive media in macroeconomics courses; and 2) measuring or knowing the level of accuracy of Online Learning Development Through Electronic Simulation Interactive Media in Economics Courses. The research method used is a Design Based Research (DBR) approach and 22 students of the Faculty of Education and Science of the Economic Education Study Program at Universitas Batanghari as research subjects. There are four stages in the Design Based Research (DBR) used, namely 1) stage I Analysis of Problems in the field; 2) Phase II Development of Online Learning Device Design and Prototype Through MISE; 3) stage III. Testing and Completing Prototypes of Online Learning Tools Through MISE; and 4) stage IV Reflection on Learning Device Products. Data collection techniques are through observation, in-depth interviews, and Focus Group Discussion (FGD). Analysis of the data used in processing the results of this research data using qualitative, quantitative, and mix method analysis. This research produces an Electronic Simulation Interactive Media (MISE) learning product that is packaged in the form of the Adobe Flash Professional CS6 Software application for macroeconomics courses with an accuracy level using the validation test of material experts and interactive learning media experts which can be seen that the results of material expert validation are 4 .5 or good and the result of media expert validation is 4.44 or good.